EVALUASI PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA PT UNILEVER INDONESIA - SETIA TJAHYANTI (Media Bisnis, 2014)
Corporate Social Responsibility is a must for companies, especially for a limited liability company. It is attested in chapter V Social and Environmental Responsibility in sections 74 subsection (1) until subsection (3) of law No. 40 year 2007 on limited liability company. This study uses secondary data and qualitative shape that is from the website of PT Unilever Indonesia regarding the activities of Corporate Social Responsibility the company has done and using research on Corporate Social Responsibility that has been done by researchers previously associated laws-an invitation about Corporate Social Responsibility. Corporate Social Responsibility is also always associated with Green Economy. The management of PT Unilever Indonesia was successfully implementing Corporate Social Responsibility as part of a strong organizational culture and also PT Unilever Indonesia has been successfully implementing adaptive culture.